IMPLEMENTASI TEKNIK STEGANOGRAFI SEBAGAI ANTI FORENSIK PENYISIPAN TEKS PADA CITRA - Eri Haryanto (Universitas Janabadra, 2016)
In the world of data and information security, there are two techniques that can be used to secure data and information, namely cryptography and steganography. In this study developed applications for the implementation of steganography techniques. Application of steganography by inserting a text message into a medium image or image file. Steganography applications created in this web-based research so that users simply access the application's domain address to encode and decode text messages.Keyword : steganografi, security, anti forensics